Antihypertensive Drugs Aliskiren, Nebivolol, and Olmesartan Reduce Hypertension by Reducing Endothelial Microparticles and Regulating Angiogenesis. Issue 3 (September 2017) - Jain, Moon; Bhosale, Vivek; Tripathi, Dipti; Singh, Himalaya; Pal, Niharika; Hanif, Kashif; Jagavelu, Kumaravelu
Abstract : Abstract: The accelerated generation of endothelial microparticles (EMPs) and impaired angiogenesis are the markers of vascular pathology during various cardiovascular and inflammatory conditions including hypertension. Because studies comparing the effects of antihypertensive agents on these 2 parameters are limited, this study was designed to compare the effects of 3 antihypertensive agents: aliskiren, nebivolol, and olmesartan, on the EMP generation and angiogenesis. Changes in the hemodynamic parameters and serum EMP count were determined after 3 weeks of the drug treatments [aliskiren (30 mg/kg), nebivolol (10 mg/kg), or olmesartan (5 mg/kg) per orally] in L-NAME–induced rat model of hypertension. The 3 drugs prevented the rise in blood pressure and EMP count to a similar extent. Furthermore, nebivolol was found to possess more potent and concentration-dependent antiangiogenic activity compared with aliskiren, whereas olmesartan was devoid of such an effect. The EMPs generated by virtue of the respective drug treatments were found to be involved in mediating the antiangiogenic effect of nebivolol and aliskiren. In addition, olmesartan treatment also resulted in the increased eNOS expression. The results of this study show that the antihypertensive drugs, viz. aliskiren, nebivolol, and olmesartan, regulate the vascular health by their differential effects on the EMP generation and angiogenesis. Abstract : Supplemental Digital Content is Available in the Text.